If p=-2,q=-1,r=3 then p3+q3+r3+3pqr=?
Answers
Answered by
7
hope this will help you.
Attachments:
![](https://hi-static.z-dn.net/files/d9e/03e9b8ad65bbae71c9fa27e39cea73c7.jpg)
Answered by
23
Given,
p = -2
q = -1
r = 3
So,
p^3 + q^3 + r^3 + 3pqr
= (-2)^3 + (-1)^3 + (3)^3 + 3 x -1 x -2 x 3
= -8 + (-1) + 27 + 9 x 2
= -8 - 1 + 27 + 18
= 27 + 18 - 8 - 1
= 45 - 9
= 36
p = -2
q = -1
r = 3
So,
p^3 + q^3 + r^3 + 3pqr
= (-2)^3 + (-1)^3 + (3)^3 + 3 x -1 x -2 x 3
= -8 + (-1) + 27 + 9 x 2
= -8 - 1 + 27 + 18
= 27 + 18 - 8 - 1
= 45 - 9
= 36
Similar questions
Social Sciences,
9 months ago
English,
9 months ago
Chemistry,
1 year ago
Chinese,
1 year ago
English,
1 year ago
Computer Science,
1 year ago
Social Sciences,
1 year ago